Magnetic Resonance Imaging Correlates of Dichotic Listening Performance in Multiple Sclerosis - Berlow, Yosef A.; Pollaro, James; Krisky, Christine; Grinstead, John; Snodgrass, Mathew; Kohout, Keith; Lewis, M. Samantha; Wilmington, Debra; Hutter, Michele; Casiana, Linda; Fitzpatrick, Mary; Lilly, David J.; Fausti, Stephen; Folmer, Robert; Bourdette, Dennis; Rooney, William D. (Seminars in Hearing, 2012)
Multiple sclerosis (MS) pathology can cause disruptions in central auditory processing. Here, we applied quantitative magnetic resonance imaging (MRI) techniques to investigate the impact of global neurodegenerative processes on dichotic listening performance in MS. We studied 28 subjects with clinically definite MS and 26 healthy controls using 3T MRI and a dichotic digits task (DDT) performed in the scanner. Subjects with MS displayed increased white matter lesions, prolonged water proton longitudinal relaxation time constants in normal appearing white matter, reduced gray matter volumes, and reduced corpus callosum areas compared with controls. No group differences were found for any of the DDT performance measures. In subjects with MS, corpus callosum area was strongly correlated with DDT performance. This relationship remained present after controlling for other measures of neuropathology, suggesting that callosal atrophy directly impacts dichotic listening performance in MS.
Keywords: multiple sclerosis; central auditory processing; magnetic resonance imaging; neurodegenerative; dichotic listening; corpus callosum